KESIAPAN MAHASISWA PROGRAM STUDI PENDIDIKAN ADMINISTRASI PERKANTORAN FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS SEBELAS MARET SURAKARTA DALAM MENGHADAPI DUNIA KERJA - Nugroho Wurianto; Tri Murwaningsih; Tutik Susilowati (JIKAP (Jurnal Informasi Dan Komunikasi Administrasi Perkantoran), 2018)
The purpose of this study is to (1) explain how the preparation of students in the Education Studies Program Administration Office of Teacher Training and Education Faculty of Sebelas Maret University Surakarta to face the world of work, (2) find out how the readiness of students in Education Studies Program Administration Office of Teaching and Training Faculty Science Education Sebelas Maret University Surakarta to face the world of work, (3) find out what obstacles and solutions made by students in the Education Studies Program Administration Faculty of Teacher Training and Education University Sebelas Maret Surakarta in preparing for the world of work.This type of research is qualitative research. The respondents of this research are students, lecturers, and head of study program that exist in Education Study Program of Administration of Teacher Training and Education Faculty of Sebelas Maret University with sampling technique using purposive sampling and snowball sampling. The result of the research shows that (1) the preparation done by the Education Administration Education Students in facing the world of work is to follow the lecture well, study the information technology, learn the English language, active in the activity outside the lecture, follow the seminar and internship DU/DI, Prodi: develop appropriate curriculum, academic interaction between lecturers and students, introduction of work world, complete learning facilities and infrastructure, establish cooperation with various agencies; (2) the majority of students of Education Administration Study Program of Teacher Training and Education Faculty of Sebelas Maret University are ready to face the world of work; (3) there are some obstacles faced by the students: lack of confidence, lack of awareness to participate in organizational activities or SMEs, lack of potential development, lack of support from nearby environment such as family and friends, hesitations to work in the field of teacher or non teacher.